Platinum and PARP Inhibitor Resistance Due to Overexpression of MicroRNA-622 in BRCA1-Mutant Ovarian Cancer - Choi, Young Eun; Meghani, Khyati; Brault, Marie-Eve; Leclerc, Lucas; He, Yizhou J.; Day, Tovah A.; Elias, Kevin M.; Drapkin, Ronny; Weinstock, David M.; Dao, Fanny; Shih, Karin K.; Matulonis, Ursula; et al. (Cell reports (Cambridge), 2016)
High-grade serous ovarian carcinomas (HGSOCs) with BRCA1/2 mutations exhibit improved outcome and sensitivity to double-strand DNA break (DSB)-inducing agents (i.e., platinum and poly(ADP-ribose) polymerase inhibitors [PARPis]) due to an underlying defect in homologous recombination (HR). However, resistance to platinum and PARPis represents a significant barrier to the long-term survival of these patients. Although BRCA1/2-reversion mutations are a clinically validated resistance mechanism, they account for less than half of platinum-resistant BRCA1/2-mutated HGSOCs. We uncover a resistance mechanism by which a microRNA, miR-622, induces resistance to PARPis and platinum in BRCA1 mutant HGSOCs by targeting the Ku complex and restoring HR-mediated DSB repair. Physiologically, miR-622 inversely correlates with Ku expression during the cell cycle, suppressing non-homologous end-joining and facilitating HR-mediated DSB repair in S phase. Importantly, high expression of miR-622 in BRCA1-deficient HGSOCs is associated with worse outcome after platinum chemotherapy, indicating microRNA-mediated resistance through HR rescue. [Display omitted] •miR-622 induces resistance to PARP inhibitors and cisplatin in BRCA1-deficient cells•miR-622 levels in BRCA1-mutant ovarian tumors correlates with survival of patients•The Ku complex is directly downregulated by miR-622 to suppress the NHEJ pathway•MiR-622 helps to balance HR and NHEJ pathways for DSB repair during the cell cycle Choi et al. show that expression of miR-622 induces resistance to PARP inhibitors and cisplatin in BRCA1-mutant ovarian tumors and correlates with survival of patients. miR-622 suppresses NHEJ by downregulating expression of the Ku complex and facilitates homologous recombination mediated repair of DNA double-strand breaks (DSBs) in the S phase of cycling cells.